2009
DOI: 10.1021/ma8025699
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Polyvinyl Chloride Sheets via Growth of Hydrophilic Polymer Brushes

Abstract: Poly(N,N-dimethylacrylamide) (PDMA) brushes were successfully grown from polyvinyl chloride (uPVC) sheets via well-controlled surface-initiated atom transfer radical polymerization (SI−ATRP). An ATRP initiator containing a chloropropionate moiety was chemically tethered onto the surface of PVC via a novel wet chemical modification. Negatively charged sulfate groups were introduced to facilitate polymerization. By incorporating a chemically cleavable group into the initiator, molecular weight, polydispersity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
78
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 62 publications
6
78
0
Order By: Relevance
“…It is reported that the higher the monomer concentration, the higher the molecular weight of grafted polymer for SI-ATRP [38]. In order to investigate the effect of molecular Table 2) monomer concentration at room temperature for 24 h for a given copper catalyst concentration.…”
Section: Molecular Weight Of Polymer Brush Evaluation By Afmmentioning
confidence: 99%
“…It is reported that the higher the monomer concentration, the higher the molecular weight of grafted polymer for SI-ATRP [38]. In order to investigate the effect of molecular Table 2) monomer concentration at room temperature for 24 h for a given copper catalyst concentration.…”
Section: Molecular Weight Of Polymer Brush Evaluation By Afmmentioning
confidence: 99%
“…The experimental details are published elsewhere. [25] Briefly, primary amine groups were first introduced onto an uPVC surface by wet chemical modification with 4-aminothiophenol, followed by coupling of hydroxy groups by a ring opening reaction of amine groups with glycidol. The ATRP initiator was then covalently coupled to the surface by an ester linkage.…”
Section: Surface Modification Of Pvcmentioning
confidence: 99%
“…By changing the monomer concentration (1 to 10%), catalyst concentration, and polymerization time various molecular weights, polydispersities, and graft densities can be obtained. [25] Characterization of PDMA Brushes on PVC Surfaces…”
Section: Surface Modification Of Pvcmentioning
confidence: 99%
See 2 more Smart Citations